Verbal Short-Term Memory and Motor Speech Processes in Broca’s Aphasia - C. Goerlich; I. Daum; I. Hertrich; H. Ackermann (Behavioural Neurology)
The present study investigated the relationship between verbal short-term memory and motor speech processes in healthy control subjects and five patients suffering from Broca's aphasia. Control subjects showed a phonological similarity effect, a word length effect and an articulatory suppression effect, supporting the hypothesis of a phonological store and an articulatory loop component of short-term memory. A similar effect of phonological similarity was observed in the aphasic patients, while the effects of word length and articulatory suppression were reduced. In control subjects, measures of short-term memory were correlated to measures of motor speech rate only if speech rate was assessed in more complex conditions (such as sentence rather than syllable repetition). There was also evidence of an association of speech impairment and short-term memory deficits in the aphasic patients.